Correction: The Influence of Second-Hand Cigarette Smoke Exposure during Childhood and Active Cigarette Smoking on Crohn's Disease Phenotype Defined by the Montreal Classification Scheme in a Western Cape Population, South Africa. - Tawanda Chivese; Tonya M Esterhuizen; Abigail Raffner Basson; Gillian Watermeyer (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0139597.].